10,000 ways to say I love you - Godek, Gregory J. P., 1955- (Naperville, Ill. : Sourcebooks Casablanca, 2009)
This is the ultimate practical, giftable resource for couples, filled with 10,000 ideas for expressing affection.
Keywords: Love -- Miscellanea; Intimacy (Psychology) -- Miscellanea